In-situ synthesis of TiO2 nanoparticles in ACF: Photocatalytic degradation under continuous flow. (1st September 2019) - Jain, Pratyush; Kumar, Arun; Verma, Nishith; Gupta, Raju Kumar
Graphical abstract: Effective degradation of MB by in-situ synthesized TiO2 nanoparticle over ACF in dynamic flow conditions. Highlights: In situ synthesis of TiO2 nanoparticles on activated carbon fiber substrate. Degradation of an organic pollutant under continuous (dynamic) flow conditions. Design of photochemical reactor for methylene blue (MB) degradation. Study of TiO2 /ACF dose and inlet concentration of MB on degradation performance. No elution or leaching of TiO2 nanoparticles in the liquid flow. Abstract: In this work, photocatalytic TiO2 nanoparticles (NPs) were in-situ synthesized on an activated carbon fiber (ACF) substrate and the prepared material was successfully used for the catalytic degradation of an organic pollutant in water under continuous (dynamic) flow conditions. Briefly, titanium tetraisopropoxide (TTIP) was immobilized within the pores of ACF using wet impregnation method followed by hydrothermal treatment. ACF played the dual role of an adsorbent as well as a support to the TiO2 NPs by preventing the NPs from eluting into the flowing effluent stream. Successful immobilization (31 mg/g) of TiO2 within the pores of ACF was confirmed through different spectroscopic techniques. The photocatalytic activity of the material for methylene blue (MB) was tested under a continuous flow in an especially designed photochemical reactor. The effects of TiO2 /ACF dose and inlet concentration of MB on degradation were studied. The data showed the prepared material to be an effective photocatalyst without leaching of the TiO2 NPs. Even at the sparse loading of TiO2 on ACF, the photocatalytic degradation kinetic rate was competitive to that reported in literature for MB degradation on the solid supported and composite catalysts. This is the first study to show an effective approach towards remediation of wastewater contaminated with methylene blue under continuous flow using the ACF-supported TiO2 NPs.